Respostas

A melhor resposta!
  • Usuário do Brainly
2013-06-26T00:17:38-03:00

Temos que:

 

4\text{x}^2-\text{x}+1=\text{x}+3\text{x}^2

 

Subtraindo 3\text{x}^2+\text{x} de ambos os membros, obtemos:

 

\text{x}^2-2\text{x}+1=0

 

Desta maneira:

 

\text{x}=\dfrac{-\text{b}\pm\sqrt{\text{b}^2-4\cdot\text{a}\cdot\text{c}}}{2\cdot\text{a}}

 

\text{x}=\dfrac{-(-2)\pm\sqrt{(-2)^2-4\cdot1\cdot1}}{2\cdot1}=\dfrac{2\pm0}{2}

 

Logo:

 

\text{x}'=\text{x}"=\dfrac{2\pm0}{2}=1

9 4 9
2013-06-26T00:20:50-03:00
4×(2) -x + 1 = x+3x (2)
passa tudo para o mesmo lado,
4×(2) -x + 1 - x -3x (2) = 0
x (2) - 2x + 1 = 0
soma e produto:
_____+______ = -b÷a
_____*_______= c÷a

x1= 1 e ×2= 1
8 2 8